Uso de nicho espacial por girinos nectônicos - PEIXOTO NETO, Carlos Alberto Algarves (2018)
Competition is among the processes that structure neotropical tadpole communities. Little is known about how the choice of microhabitat influences the distribution of neotropical tadpoles. We investigated whether the tadpoles of Scinax x-signatus and Scinax fuscomarginatus overlapped the spatial niche and presented a segregated distribution in 15 temporary temporary ponds on the island of Maranhão, northeastern Brazil. In laboratory, we tested the hypothesis that large size tadpoles of S. x-signatus would not be affected in the use of spatial resources for foraging by small size tadpoles of the same species or small size tadpoles of S. fuscomarginatus. For laboratory experiments, tadpoles of different spawnings were collected in temporary open water bodies. After acclimatization we filmed the interactions between species and different sizes of tadpoles in an experimental design with focal tadpoles of Scinax x-signatus of small size (n = 30), focal larvae of S. x-signatus of large size (n = 30) and tadpoles of S. fuscomarginatus (n = 60). Slides with food (algae) arranged in the aquarium made it possible to evaluate the use of space by tadpoles. The use of the height of the slide (Vertical Position) and displacement among different slides (Horizontal Position) by tadpoles were obtained by analysing the videos. For the analysis of spatial niche overlap and observed co-occurrence pattern we used the EcoSim software. To identify the preference in the use of the space we used mixed models, function lme with a posterior test of Tukey in the software R. In the ponds, the species are overlapping in the use of environmental resources, but they differ in the frequency of use. In the experiment, the small focal tadpoles of S. x-signatus, which occupy smaller to medium depths, altered the horizontal position in the presence of coespecific larger tadpoles or tadpoles of S. fuscomarginatus. While large focal tadpoles, which occupy the greater depths, in the presence of a coespecific or heterospecific tadpole changed the height of foraging. Thus, the small tadpoles seem to try to avoid interaction, whereas the large tadpoles seem to alter the position in the water column to occupy the space that smaller tadpoles can use.